Salinity Affects Freshwater Invertebrate Traits and Litter Decomposition - Abelho, Manuela (2021)
We evaluated the effect of seawater intrusion in coastal ecosystems on the freshwater invertebrate community and on leaf litter decomposition under realistic scenarios in six outdoor freshwater mesocosms containing fauna and flora, to which increasing volumes of seawater were added. The resulting salinity values were 0.28 (control, freshwater only), 2.0, 3.3, 5.5, 9.3, and 15.3 mS cm1. The effect of salinity was assessed for 65 days after seawater intrusion, by computing the deviation of values in each treatment in relation to the control. Our results show that seawater intrusion into freshwaters will affect the invertebrate communities and organic matter decomposition, with salinities of up to 3.3–5.5 mS cm1 having opposite effects to salinities of more than 9.3 mS cm1. There was a net negative effect of the two highest salinities on mass loss and richness of the invertebrates associated with the decomposing leaves. Regarding the invertebrate communities of the mesocosms, there was a net negative effect of the intermediate salinity levels on abundance and richness. Invertebrate life cycle traits conferring resilience and resistance tended to increase with low and decrease with high salinity values, while avoidance traits showed an opposite trend, and these responses were more pronounced on the later stage community. These wave-like responses of the invertebrate species traits to increasing salinity suggest that the life-history and physiological adaptations most suitable to cope with osmotic stress will differ between low and high salinity levels.